The influence of coronary plaque morphology assessed by optical coherence tomography on final microvascular function after stenting in patients with ST-elevation myocardial infarction - De Maria, GL; Patel, N; Wolfrum, M; Fahrni, G; Kassimis, G; Porto, I; Dawkins, S; Choudhury, RP; Forfar, JC; Prendergast, BD; Channon, KM; Kharbanda, RK; et al. (Lippincott, Williams & Wilkins, 2017)
Objectives The index of microcirculatory resistance (IMR) provides a reproducible assessment of the status of coronary microvasculature in patients with ST-elevation myocardial infarction (STEMI). Frequency-domain optical coherence tomography (FD-OCT) enables detailed assessment of the morphology of coronary plaque.